A Digital Home-Based Health Care Center for Remote Monitoring of Side Effects During Breast Cancer Therapy: Prospective, Single-Arm, Monocentric Feasibility Study - Hübner, Hanna; Wurmthaler, Lena; Goossens, Chloe; Ernst, Mathias; Mocker, Alexander; Krückel, Annika; Kallert, Maximilian; Geck, Jürgen; Limpert, Milena; Seitz, Katharina; Rübner, Matthias; Kreis, Philipp; et al. (JMIR Cancer, 2025)
Background: The introduction of oral anticancer therapies has, at least partially, shifted treatment from clinician-supervised hospital care to patient-managed home regimens. However, patients with breast cancer receiving oral cyclin-dependent kinase 4/6 inhibitor therapy still require regular hospital visits to monitor side effects. Telemonitoring has the potential to reduce hospital visits while maintaining quality care. Objective: This study aims to develop a digital home-based health care center (DHHC) for acquiring electrocardiograms (ECGs), white blood cell (WBC) counts, side effect photo documentation, and patient-reported quality of life (QoL) data. Methods: The DHHC was set up using an Apple Watch Series 6 (ECG measurements), a HemoCue WBC DIFF Analyzer (WBC counts), an iPhone SE (QoL assessments and photo documentation), a TP-Link M7350-4G Wi-Fi router, and a Raspberry Pi 4 Model B. A custom-built app stored and synchronized remotely collected data with the clinic. The feasibility and acceptance of the DHHC among patients with breast cancer undergoing cyclin-dependent kinase 4/6 inhibitor therapy were evaluated in a prospective, single-arm, monocentric study. Patients (n=76) monitored side effects—ECGs, WBC counts, photo documentation, and QoL—at 3 predefined time points: study inclusion (on-site), day 14 (remote), and day 28 (remote). After the study completion, patients completed a comprehensive questionnaire on user perception and feasibility. Adherence to scheduled visits, the success rate of the data transfer, user perception and feasibility, and the clinical relevance of remote measurements were evaluated. Results: Mean adherence to the planned remote visits was 63% on day 14 and 37% on day 28. ECG measurements were performed most frequently (day 14: 57/76, 75%; day 28: 31/76, 41%). The primary patient-reported reason for nonadherence was device malfunction. The expected versus the received data transfer per patient was as follows: ECGs: 3 versus 3.04 (SD 1.9); WBC counts: 3 versus 2.14 (SD 1.14); QoL questionnaires: 3 versus 2.5 (SD 1.14); and photo documentation: 6 versus 4.4 (SD 3.36). Among patients, 81% (55/68) found ECG measurements easy, 82% (55/67) found photo documentation easy, and 48% (33/69) found WBC measurements easy. Additionally, 61% (40/66) of patients felt comfortable with self-monitoring and 79% (54/68) were willing to integrate remote monitoring into their future cancer care. Therapy-induced decreased neutrophil count was successfully detected (P<.001; mean baseline: 4.3, SD 2.2, ×109/L; on-treatment: 1.8, SD 0.8, ×109/L). All-grade neutropenia and corrected QT interval prolongations were detected in 80% (55/68) and 2% (1/42) of patients, respectively. Conclusions: Adherence to scheduled remote visits was moderate, with nonadherence primarily attributed to device-related complications, which may have also affected the success rate of data transfer. Overall, patients considered remote monitoring useful and feasible. The prevalence of reported adverse events was comparable to existing literature, suggesting clinical potential. This initial feasibility study highlights the potential of the DHHC.
CRIS-Team Scopus Importer:2025-05-30
Keywords: breast cancer; CDK4/6 inhibitor; cyclin-dependent kinase 4/6 inhibitor; digital medicine; mobile phone; remote monitoring; telehealth

Attrition in the First Three Therapy Lines in Patients with Advanced Breast Cancer in the German Real-World PRAEGNANT Registry - Hartkopf, Andreas D.; Walter, Christina B.; Kolberg, Hans Christian; Hadji, Peyman; Tesch, Hans; Fasching, Peter; Ettl, Johannes; Lüftner, Diana; Wallwiener, Markus; Müller, Volkmar; Beckmann, Matthias; Belleville, Erik; et al. (Geburtshilfe und Frauenheilkunde, 2024)
Background With more effective therapies for patients with advanced breast cancer (aBC), therapy sequences are becoming increasingly important. However, some patients might drop out of the treatment sequence due to deterioration of their life status. Since little is known about attrition in the real-world setting, this study assessed attrition in the first three therapy lines using a real-world registry. Methods Patients with information available on the first three therapy lines were selected from the German PRAEGNANT registry (NCT02338167). Attrition was determined for each therapy line using competing risk analyses, with the start of the next therapy line or death as endpoints. Additionally, a simple attrition rate was calculated based on the proportion of patients who completed therapy but did not start the next therapy line. Results Competitive risk analyses were performed on 3988 1st line, 2651 2nd line and 1866 3rd line patients. The probabilities of not starting the next therapy line within 5 years after initiation of 1st, 2nd and 3rd line therapy were 30%, 24% and 24% respectively. Patients with HER2-positive disease had the highest risk for attrition, while patients with HRpos/HER2neg disease had the lowest risk. Attrition rates remained similar across molecular subgroups in the different therapy lines. Conclusion Attrition affects a large proportion of patients with aBC, which should be considered when planning novel therapy concepts that specifically address the sequencing of therapies. Taking attrition into account could help understand treatment effects resulting from sequential therapies and might help develop treatment strategies that specifically aim at maintaining quality of life.
CRIS-Team Scopus Importer:2024-06-14
Keywords: advanced breast cancer; clinical trials; de novo metastatic breast cancer; recurrent breast cancer metastases

Characteristics and prognosis of patients with primary metastatic disease vs. recurrent HER2-negative, hormone receptor-positive advanced breast cancer - Walter, Christina B.; Hartkopf, Andreas D.; Hein, Alexander; Fasching, Peter; Kolberg, Hans Christian; Hadji, Peyman; Tesch, Hans; Häberle, Lothar; Ettl, Johannes; Lüftner, Diana; Wallwiener, Markus; Müller, Volkmar; et al. (BREAST, 2025)
Background: Patients with first-line metastatic breast cancer (MBC) comprise patients with de novo metastases (dnMBC) or recurrent disease after primary breast cancer (rMBC). This analysis aimed to explore the prognostic value of dnMBC versus rMBC overall and particularly in subgroups according to age and metastasis site, in addition to other prognostic clinicopathological parameters in a first-line, hormone receptor (HR)-positive, HER2-negative (HRpos/HER2neg) population. Methods: Within the prospective PRAEGNANT MBC registry (NCT02338167), 508 HRpos/HER2neg patients, receiving first-line treatment for advanced disease, were identified. Clinicopathological parameters (age, body mass index, performance status, tumor grading, metastasis site and therapy) were assessed according to metastatic status (dnMBC, rMBC within 5 years of primary diagnosis (rMBC <5 years), rMBC after more than 5 years (rMBC ≥5 years)). Cox regression analyses were performed to investigate whether metastatic status influences progression-free survival (PFS) and overall survival (OS). Results: De novo metastatic disease was present in 180 patients (35.4 %), whereas 132 patients (26.0 %) had rMBC <5 years and 196 patients (38.6 %) had rMBC ≥5 years. Patients with dnMBC had the most favorable prognosis. Relative to dnMBC, hazard ratios for PFS were 1.75 (95%CI: 1.31–2.34) in rMBC<5 years and 1.25 (95%CI: 0.94–1.65) for rMBC ≥5 years. Subgroup-specific differences were not observed. Conclusion: HRpos/HER2neg first-line MBC patients have a more favorable prognosis if the disease was previously not treated. This difference was similar across all examined clinicopathological parameters. It may therefore be beneficial to incorporate MBC categories as a stratification factor in clinical trials.
CRIS-Team Scopus Importer:2025-02-21
Keywords: Advanced breast cancer; de novo metastatic breast cancer; First line therapy; HER2-negative; Hormone receptor-positive; Metastasis

Effect of delayed isolation of peripheral blood mononuclear cells on cell viability and functionality - Lehle, Sarah; Völkl, Simon; Seitz, Katharina; Goossens, Chloe; Emons, Julius; Rübner, Matthias; Uhrig, Sabrina; Ziegler, Philipp; Theuser, Anna Katharin; Beckmann, Matthias; Fasching, Peter; Hübner, Hanna (Bmc Immunology, 2025)
Background: Peripheral blood mononuclear cells (PBMCs) are valuable biomarkers, providing crucial insights into the patients’ immune system. Reliable biobanking of PBMCs is essential to minimize heterogeneity. In multicenter trials, blood sample transportation to central laboratories can increase the time between blood collection and PBMC isolation. This study evaluated the effect of prolonged blood hold time on PBMC viability and cytotoxicity. Methods: From July 2021 to May 2023, 104 patients with early HER2-positive breast cancer were enrolled in the NeoOn trial, of whom 49 patients were included in this subproject. PBMCs were isolated ≤ 6 hours (h) or ≥ 20 h after blood collection. PBMC yield and viability were determined using the LUNA-II Automated Cell Counter. Flow cytometry was used to quantify in vitro cytotoxicity, the percentage of natural killer (NK) and T cells, as well as apoptotic and necrotic cells. Results: Isolating PBMCs ≥ 20 h resulted in a higher cell yield, but lower NK cell viability compared to PBMCs ≤ 6 h. PBMCs ≥ 20 h were less robust to thawing and showed higher loss during recovery. Compared to PMBCS ≤ 6 h, PBMCs ≥ 20 h exhibited lower antibody-mediated cytotoxicity (p ≤ 0.0001) and antibody-dependent phagocytosis (p < 0.0051). While the percentage of T and NK cells and the T cell viability remained unaffected by hold time, the percentage of apoptotic NK cells was higher for PBMCs ≥ 20 h (41.0 ± 12.9% vs. 23.8 ± 13.4%; p = 0.0364). Conclusions: Extended blood storage time caused increased apoptosis and necrosis of NK cells, adversely affecting PBMC quality and reducing NK cell related functionality. Hence, blood hold time should be minimized to maintain PBMC integrity and NK cell functionality for in vitro biomarker assays. Trial registration: Trial registration number: EudraCT 2020-001943-21. Date of registration: December 29th 2020
CRIS-Team Scopus Importer:2025-04-01
Keywords: Biobanking; Cell viability; Cytotoxicity; PBMCs; Phase IV clinical trial

Invasive disease-free and overall survival after (neo)adjuvant chemotherapy in postmenopausal patients with hormone receptor-positive, HER2-negative early breast cancer treated with upfront letrozole: Experiences from the phase IV PreFace trial - Beierlein, Milena; Häberle, Lothar; Nabieva, Naiba; Maass, Nicolai; Aktas, Bahriye; Kümmel, Sherko; Thomssen, Christoph; Wolf, Christopher; Kolberg, Hans Christian; Brucker, Cosima; Janni, Wolfgang; Dall, Peter; et al. (International Journal of Cancer, 2025)
Patients with hormone receptor-positive (HRpos), HER2-negative (HER2neg) breast cancer (BC) benefit less from neoadjuvant chemotherapy (NACT) than patients with triple-negative and HER2-positive BC. In this retrospective analysis of the phase IV PreFace clinical trial (NCT01908556), where postmenopausal HRpos BC patients (n = 3297) were treated with 5-year upfront adjuvant letrozole therapy, we evaluated the prognosis of patients treated with adjuvant versus neoadjuvant chemotherapy in HRpos/HER2neg early-stage BC. HRpos/HER2neg patients with information on (neo)adjuvant chemotherapy (n = 2895) were retrospectively selected from all patients enrolled in the PreFace trial. Invasive disease-free survival (iDFS) and overall survival (OS) were compared between patient groups that were treated with neoadjuvant or adjuvant chemotherapy. Chemotherapy was given to 1051 patients (36.3% of all patients), of which 874 (83.2%) received adjuvant chemotherapy and 177 (16.8%) NACT. Pathologic complete response (pCR) rate in the NACT group was 6.9%. Patients treated with NACT had a worse outcome than those treated with adjuvant chemotherapy (5-year iDFS rate 81% vs. 88%; 5-year OS rate 89% vs. 93%). This effect was maintained after adjusting for age, BMI, lymph node status, grading, tumor size, and histology (hazard ratio for iDFS: 1.95 (95%CI: 1.28–2.95); hazard ratio for OS: 2.13 (95%CI: 1.24–3.66)). Further adjustment for taxane-based regimes did not alter results. In conclusion, in this retrospective analysis of patients with early-stage HRpos/HER2neg BC, patients with NACT had a more unfavorable prognosis than patients treated adjuvantly, independent of patient and tumor characteristics. Prognosis of neoadjuvant patients might be affected by resistance mechanisms, warranting further investigation.
CRIS-Team Scopus Importer:2025-07-25
Keywords: adjuvant chemotherapy; breast cancer; hormone receptor-positive/HER2-negative; neoadjuvant chemotherapy; phase IV clinical trial

Long-term Follow-up and Safety of Patients after an Upfront Therapy with Letrozole for Early Breast Cancer in Routine Clinical Care – The PreFace Study - Hack, Carolin; Maass, Nicolai; Aktas, Bahriye; Kümmel, Sherko; Thomssen, Christoph; Wolf, Christopher; Kolberg, Hans Christian; Brucker, Cosima; Janni, Wolfgang; Dall, Peter; Schneeweiss, Andreas; Marme, Frederik; et al. (Geburtshilfe und Frauenheilkunde, 2023)
Introduction Adjuvant treatment of patients with early-stage breast cancer (BC) should include an aromatase inhibitor (AI). Especially patients with a high recurrence risk might benefit from an upfront therapy with an AI for a minimum of five years. Nevertheless, not much is known about the patient selection for this population in clinical practice. Therefore, this study analyzed the prognosis and patient characteristics of postmenopausal patients selected for a five-year upfront letrozole therapy. Patients and Methods From 2009 to 2011, 3529 patients were enrolled into the adjuvant phase IV PreFace clinical trial (NCT01908556). Postmenopausal hormone receptor-positive BC patients, for whom an upfront five-year therapy with letrozole (2.5 mg/day) was indicated, were eligible. Disease-free survival (DFS), overall survival (OS) and safety in relation to patient and tumor characteristics were assessed. Results 3297 patients started letrozole therapy. The majority of patients (n = 1639, 57%) completed the five-year treatment. 34.5% of patients continued with endocrine therapy after the mandated five-year endocrine treatment. Five-year DFS rates were 89% (95% CI: 88-90%) and five-year OS rates were 95% (95% CI: 94-96%). In subgroup analyses, DFS rates were 83%, 84% and 78% for patients with node-positive disease, G3 tumor grading, and pT3 tumors respectively. The main adverse events (any grade) were pain and hot flushes (66.8% and 18.3% of patients). Conclusions The risk profile of postmenopausal BC patients selected for a five-year upfront letrozole therapy showed a moderate recurrence and death risk. However, in subgroups with unfavorable risk factors, prognosis warrants an improvement, which might be achieved with novel targeted therapies.
CRIS-Team Scopus Importer:2024-12-16
Keywords: aromatase inhibitors; early breast cancer; hormone therapy; letrozole; prognosis

Prediction of pathological complete response after neoadjuvant chemotherapy for HER2-negative breast cancer patients with routine immunohistochemical markers. - Häberle, Lothar; Erber, Ramona; Gaß, Paul; Hein, Alexander; Niklos, Melitta; Volz, Bernhard; Hack, Carolin; Schulz-Wendtland, Rüdiger; Hübner, Hanna; Goossens, Chloe; Christgen, Matthias; Dörk, Thilo; et al. (Breast Cancer Research, 2025)
BACKGROUND: Pathological complete response (pCR) is an established surrogate marker for prognosis in patients with breast cancer (BC) after neoadjuvant chemotherapy. Individualized pCR prediction based on clinical information available at biopsy, particularly immunohistochemical (IHC) markers, may help identify patients who could benefit from preoperative chemotherapy. METHODS: Data from patients with HER2-negative BC who underwent neoadjuvant chemotherapy from 2002 to 2020 (n = 1166) were used to develop multivariable prediction models to estimate the probability of pCR (pCR-prob). The most precise model identified using cross-validation was implemented in an online calculator and a nomogram. Associations among pCR-prob, prognostic IHC3 distant recurrence and disease-free survival were studied using Cox regression and Kaplan-Meier analyses. The model's utility was further evaluated in independent external validation cohorts. RESULTS: 273 patients (23.4%) achieved a pCR. The most precise model had across-validated area under the curve (AUC) of 0.84, sensitivity of 0.82, and specificity of 0.71. External validation yielded AUCs between 0.75 (95% CI, 0.70-0.81) and 0.83 (95% CI, 0.78-0.87). The higher the pCR-prob, the greater the prognostic impact of pCR status (presence/absence): hazard ratios decreased from 0.55 (95% central range, 0.07-1.77) at 0% to 0.20 (0.11-0.31) at 50% pCR-prob. Combining pCR-prob and IHC3 score further improved the precision of disease-free survival prognosis. CONCLUSIONS: A pCR prediction model for neoadjuvant therapy decision-making was established. Combining pCR and recurrence prediction allows identification of not only patients who benefit most from neoadjuvant chemotherapy, but also patients with a very unfavorable prognosis for whom alternative treatment strategies should be considered.
EVALuna2:585357

Prognosis prediction with the IHC3 score in patients with node-negative, hormone receptor-positive, HER2-negative early breast cancer - Seitz, Katharina; Goossens, Chloe; Hübner, Hannah; Gaß, Paul; Uhrig, Sabrina; Heindl, Felix; Emons, Julius; Rübner, Matthias; Anetsberger, Daniel; Hartmann, Arndt; Beckmann, Matthias; Erber, Ramona; et al. (ESMO Open, 2024)
Background: Prognostication has been used to identify patient populations that could potentially benefit from treatment de-escalation. In patients with hormone receptor-positive (HRpos), human epidermal growth factor receptor 2-negative (HER2neg) early breast cancer (eBC), treatment de-escalation classically involved omitting chemotherapy. With recently developed specialized therapies that require hands-on side-effect management, the therapeutic landscape is changing and therapy decisions are no longer based only on prognosis, but also consider potential side-effects. Therefore, identification of patient groups based on prognostication has gained importance. Materials and methods: In this retrospective analysis, a population of 2359 node-negative HRpos/HER2neg eBC patients was selected from all patients treated at the University Breast Center of Franconia, Germany between 2002 and 2021. The prognostic value of the IHC3 score (incorporating immunohistochemical measurements of the estrogen and progesterone receptor status and Ki-67) with clinical parameters (lymph node status, tumor stage, grading) regarding invasive disease-free survival (iDFS) and overall survival (OS) was assessed. Results: IHC3 positively correlated with Ki-67 expression and inversely correlated with hormone receptor expression. IHC3 categorized into quartiles identified patients with a more unfavorable prognosis: 5-year and 10-year iDFS rates for patients in the highest versus the lowest quartile were 84% versus 95% and 70% versus 88%, respectively. A sensitivity analysis of distant disease-free survival showed similar results to those of iDFS. Five-year and 10-year OS rates for patients in the highest versus the lowest quartile were, respectively, 92% versus 97% and 81% versus 92%. Conclusions: IHC3 is able to define prognostic groups in patients with node-negative, HRpos/HER2neg eBC. Node-negative patients with a high IHC3 score had the worst prognosis, which was comparable to that of node-positive patients described in recent trials. This simple and cost-effective tool could thus potentially aid in identifying patient groups for innovative therapeutic approaches.
CRIS-Team Scopus Importer:2024-11-01
Keywords: early breast cancer; hormone receptor-positive; IHC3; molecular marker; prognosis

Prognostic impact of selection criteria of current adjuvant endocrine therapy trials NATALEE and monarchE in postmenopausal HRpos/HER2neg breast cancer patients treated with upfront letrozole - Fasching, Peter; Hack, Carolin; Nabieva, Naiba; Maass, Nicolai; Aktas, Bahriye; Kümmel, Sherko; Thomssen, Christoph; Wolf, Christopher; Kolberg, Hans Christian; Brucker, Cosima; Janni, Wolfgang; Dall, Peter; et al. (European Journal of Cancer, 2024)
Background: The monarchE and NATALEE trials demonstrated the benefit of CDK4/6 inhibitor (CDK4/6i) therapy in adjuvant breast cancer (BC) treatment. Patient selection, based on clinical characteristics, delineated those at high (monarchE) and high/intermediate recurrence risk (NATALEE). This study employed a historical patient cohort to describe the proportion and prognosis of patients eligible for adjuvant CDK4/6i trials. Methods: Between 2009 and 2011, 3529 patients were enrolled in the adjuvant PreFace clinical trial (NCT01908556). Eligibility criteria included postmenopausal patients with hormone receptor-positive (HRpos) BC for whom a five-year upfront therapy with letrozole was indicated. Patients were categorized into prognostic groups according to monarchE and NATALEE inclusion criteria, and their invasive disease-free survival (iDFS) and overall survival (OS) were assessed. Results: Among 2891 HRpos patients, 384 (13.3 %) met the primary monarchE inclusion criteria. The majority (n = 261) qualified due to having ≥ 4 positive lymph nodes. For NATALEE, 915 out of 2886 patients (31.7 %) met the eligibility criteria, with 126 patients (13.7 %) being node-negative. Patients from monarchE with ≥ 4 positive lymph nodes and NATALEE with stage III BC exhibited the poorest prognosis (3-year iDFS rate 0.87). Patients ineligible for the trials demonstrated prognoses similar to the most favorable patient groups within the eligibility criteria. Conclusion: Patient populations eligible for monarchE and NATALEE trials differed. Nearly a third of the postmenopausal HRpos population, previously under upfront letrozole treatment, met the NATALEE prognostic eligibility criteria. As certain eligible groups had a prognosis similar to non-eligible patients, it might be interesting to explore additional patient groups for CDK4/6i therapy.
CRIS-Team Scopus Importer:2024-08-02
Keywords: Aromatase inhibitors; CDK4/6 inhibitors; Early breast cancer; Hormone therapy; Letrozole; Prognosis

Prognostic impact of the choice of chemotherapy after first-line CDK4/6 inhibitor therapy in patients with metastatic hormone receptor-positive, HER2-negative breast cancer - Michel, Laura L.; Ziegler, Philipp; Kreis, Philipp; Hartkopf, Andreas D.; Wallwiener, Markus; Häberle, Lothar; John, Nelson; Kolberg, Hans Christian; Hadji, Peyman; Tesch, Hans; Ettl, Johannes; Lüftner, Diana; et al. (European Journal of Cancer, 2025)
Introduction: Whereas CDK4/6 inhibitors (CDK4/6i) are the standard first-line therapy for patients with hormone receptor-positive (HRpos), HER2-negative (HER2neg) metastatic breast cancer, guidelines on treatment options after progression on CDK4/6i are more diverse. Chemotherapy is recommended if a patient develops endocrine resistance or experiences a visceral crisis. However, the impact of the choice of chemotherapy remains unknown. Methods: HRpos/HER2neg patients who received first-line CDK4/6i, followed by second-line chemotherapy (N = 215) were selected from the prospective PRAEGNANT registry (NCT02338167). Cox regression analyses were used to evaluate the correlation between the choice of chemotherapy (capecitabine monotherapy, capecitabine + bevacizumab, taxane monotherapy, taxane + bevacizumab, anthracycline, other chemotherapeutics) and progression-free survival (PFS) and overall survival (OS). Results: Patients who received second-line chemotherapy mostly had high-grade tumors (G2: 62.3 %, G3: 33.3 %), visceral metastases (62.3 %) and developed metastatic disease following a primary breast cancer diagnosis (73.8 %). Capecitabine was the most common regimen (25.1 %), followed by taxane + bevacizumab (17.2 %). When adjusting for other prognostic factors (age, BMI, grading, ECOG, metastasis group and time to metastases), the choice of chemotherapy did not influence PFS (p = 0.16) nor OS (p = 0.47). Adjusted hazard ratios for PFS were lowest in regimens with bevacizumab (capecitabine as reference; capecitabine + bevacizumab: 0.53 (95 %CI: 0.29, 0.97); taxane + bevacizumab: 0.64 (95 %CI 0.35, 1.15)). Conclusion: Although the choice of chemotherapy post-CDK4/6i did not significantly affect PFS or OS, combinations with bevacizumab may have some benefit. Nevertheless, considering side effects may be most important when choosing the type of second-line chemotherapy.
CRIS-Team Scopus Importer:2025-08-15
Keywords: CDK4/6 inhibitor; Chemotherapy; Hormone receptor-positive; Metastatic breast cancer; Prognosis

Real-world utilization of aromatase inhibitors, tamoxifen, and ovarian function suppression in premenopausal patients with early hormone receptor-positive, HER2-negative breast cancer with increased recurrence risk - Müller, Volkmar; Hörner, Manuel; Thill, Marc; Banys-Paluchowski, Maggie; Schmatloch, Sabine; Fasching, Peter; Harbeck, Nadia; Langanke, Dagmar; Uhrig, Sabrina; Häberle, Lothar; Fischer, Dorothea; Hein, Alexander; et al. (BREAST, 2025)
Background: The optimal adjuvant endocrine treatment in premenopausal patients with hormone receptor-positive, HER2-negative (HRpos/HER2neg) early breast cancer (eBC) remains debated, particularly the choice between aromatase inhibitors plus ovarian function suppression (AI + OFS) or tamoxifen (TAM) with or without additional OFS. This study assessed the use of adjuvant endocrine therapies for premenopausal patients with intermediate/high-risk HRpos/HER2neg eBC. Methods: CLEAR-B (AGO-B-059; NCT05870813) was a retrospective study analyzing data, collected from January 2016 to June 2019 and from January 2022 to December 2023 during the certification process of breast centers in Germany. Premenopausal patients with HRpos/HER2neg intermediate/high-risk eBC were eligible. Patient and disease characteristics, in addition to recommended and received adjuvant treatments, were evaluated. Results: The number of registered patients was 3137, of whom 2789 had complete information on endocrine treatments (1717 for 2016–2019 and 1072 for 2022–2023). In 2016–2019, 8.4 % of the patients were recommended to be treated with AI + OFS, whereas in 2022–2023, the proportion of patients with a treatment recommendation for AI + OFS rose to 42.1 %. In 2016–2019, TAM monotherapy was most frequently recommended (80.8 %). Conversely, TAM + OFS was not commonly recommended (9.3 % in 2016–2019 and 16.5 % in 2022–2023). While no clear association between tumor stage and chosen endocrine therapy was found in 2016–2019, most patients with ≥stage IIA were recommended to be treated with AI + OFS in 2022–2023. Conclusion: This analysis shows that treatment recommendation for AI + OFS in premenopausal patients with HRpos/HER2neg eBC increased relevantly in the past years, reflecting latest guideline recommendations.
CRIS-Team Scopus Importer:2025-04-01
Keywords: Aromatase inhibitor; Early breast cancer; Endocrine therapy; Hormone receptor-positive; Tamoxifen

Susceptibility gene mutations in germline and tumors of patients with HER2-negative advanced breast cancer - Fasching, Peter; Hu, Chunling; Hart, Steven N.; Rübner, Matthias; Polley, Eric C.; Gnanaolivu, Rohan D.; Hartkopf, Andreas D.; Hübner, Hanna; Janni, Wolfgang; Hadji, Peyman; Tesch, Hans; Uhrig, Sabrina; et al. (npj Breast Cancer, 2024)
Germline mutations in BRCA1 and BRCA2 (gBRCA1/2) are required for a PARP inhibitor therapy in patients with HER2-negative (HER2−) advanced breast cancer (aBC). However, little is known about the prognostic impact of gBRCA1/2 mutations in aBC patients treated with chemotherapy. This study aimed to investigate the frequencies and prognosis of germline and somatic BRCA1/2 mutations in HER2- aBC patients receiving the first chemotherapy in the advanced setting. Patients receiving their first chemotherapy for HER2- aBC were retrospectively selected from the prospective PRAEGNANT registry (NCT02338167). Genotyping of 26 cancer predisposition genes was performed with germline DNA of 471 patients and somatic tumor DNA of 94 patients. Mutation frequencies, progression-free and overall survival (PFS, OS) according to germline mutation status were assessed. gBRCA1/2 mutations were present in 23 patients (4.9%), and 33 patients (7.0%) had mutations in other cancer risk genes. Patients with a gBRCA1/2 mutation had a better OS compared to non-mutation carriers (HR: 0.38; 95%CI: 0.17–0.86). PFS comparison was not statistically significant. Mutations in other risk genes did not affect prognosis. Two somatic BRCA2 mutations were found in 94 patients without gBRCA1/2 mutations. Most frequently somatic mutated genes were TP53 (44.7%), CDH1 (10.6%) and PTEN (6.4%). In conclusion, aBC patients with gBRCA1/2 mutations had a more favorable prognosis under chemotherapy compared to non-mutation carriers. The mutation frequency of 5% with gBRCA1/2 mutations together with improved outcome indicates that germline genotyping of all metastatic patients for whom a PARP inhibitor therapy is indicated should be considered.
CRIS-Team Scopus Importer:2024-07-19

Systematic Comparison of ECG Delineation Algorithm Performance on Smartwatch Data - Jäger, Katharina; Nissen, Michael; Flaucher, Madeleine; Graf, Luisa; Joanidopoulos, Joana; Anneken, Lars; Hübner, Hanna; Goossens, Chloe; Titzmann, Adriana; Pontones, Constanza; Fasching, Peter; Beckmann, Matthias; et al. (IEEE Access, 2024)
Cardiovascular diseases are the leading cause of global mortality, necessitating early detection and continuous monitoring for timely interventions. Smartwatches with electrocardiogram (ECG) recording capabilities enable real-time, at-home cardiac monitoring. Specific ECG characteristics can provide insights into cardiovascular diseases. The delineation of ECGs, which is the identification of fiducial points (such as onsets, offsets, and peaks), is a time-consuming task. Automated ECG delineation can enhance this process, but existing research comparing available algorithms is limited. Furthermore, to the best of our knowledge, none have addressed single-lead ECGs from smartwatches, which can be noisy and unfiltered. Thus, this study evaluates the best-performing open-source algorithm for single-lead and smartwatch ECG data. We used two public datasets (Lobachevsky University Database, QT Database) and two smartwatch datasets (SmartHeartWatch Dataset, SMART Start Dataset) including two devices (AppleWatch, Withings ScanWatch). Algorithms from three toolkits (NeuroKit, ECGKit, ECGdeli) were assessed based on the time deviation between algorithm outputs and reference annotations, sensitivity, true positives, and false negatives. Results were further evaluated against the Common Standards for Quantitative Electrocardiography (CSE) recommendations. ECGdeli outperformed the other algorithms. For QRS on- and offset, ECGkit shows comparable sensitivity, but otherwise lower scores. NeuroKit consistently shows lower sensitivity across all four data sets, however, the temporal deviation between detected point and reference was higher. Overall, sensitivity scores were higher for Apple Watch data compared to Withings ScanWatch data. This study demonstrates that segmentation algorithms are applicable to single-lead smartwatch ECG data, with ECGdeli being the most stable overall, and NeuroKit recommended for scenarios prioritizing the temporal accuracy of detected points.
CRIS-Team Scopus Importer:2024-11-15
Keywords: Cardiovascular Diseases; ECG Segmentation; Mobile Health; Wearable Devices

The impact of physical activity on progression-free and overall survival in metastatic breast cancer based on molecular subtype - Ziegler, Philipp; Hartkopf, Andreas D.; Wallwiener, Markus; Häberle, Lothar; Kolberg, Hans Christian; Hadji, Peyman; Tesch, Hans; Ettl, Johannes; Lüftner, Diana; Müller, Volkmar; Michel, Laura L.; Belleville, Erik; et al. (BMC Cancer, 2024)
Background: Although adequate physical activity has been shown to be beneficial in early breast cancer, evidence in metastatic breast cancer is sparse and contradictory, which could be related to distinct effects of physical activity on the different molecular cancer subtypes. Therefore, we here evaluated the effect of physical activity on progression-free and overall survival (PFS, OS) in metastatic breast cancer, specifically looking at molecular subtypes. Methods: International Physical Activity Questionnaire (IPAQ) questionnaires, filled out by patients enrolled in the prospective PRAEGNANT registry (NCT02338167; n = 1,270) were used to calculate metabolic equivalent task (MET) minutes, which were subsequently categorized into low (n = 138), moderate (n = 995) or high IPAQ categories (n = 137). Cox regression analyses were used to evaluate the impact of IPAQ categories and its interaction with molecular subtypes on PFS and OS. Results: Patient and tumor characteristics were equally distributed across IPAQ categories. HER2pos, HRpos and TNBC were present in 23.1%, 65.7% and 11.2% of patients, respectively. IPAQ scores did not have an impact on PFS and OS in addition to established prognostic factors, either overall or in particular molecular subtypes (PFS: p = 0.33 and OS: p = 0.08, likelihood ratio test). Exploratory analyses showed higher overall survival rates for high IPAQ categories compared to low/moderate IPAQ categories in luminal B-like breast cancer. Conclusions: Self-reported physical activity using the IPAQ questionnaire did not significantly affect PFS or OS in patients suffering from metastatic breast cancer. Nevertheless, some hypothesis-generating differences between molecular subtypes could be observed, which may be interesting to evaluate further.
CRIS-Team Scopus Importer:2024-10-25
Keywords: IPAQ; Metastatic breast cancer; Molecular subtype; Physical activity

Update Breast Cancer 2024 Part 2 – Patients with Early Stage Breast Cancer - Janni, Wolfgang; Kolberg, Hans Christian; Hartkopf, Andreas D.; Fehm, Tanja N.; Welslau, Manfred; Müller, Volkmar; Schütz, Florian; Fasching, Peter; Jackisch, Christian; Marme, Frederik; Hörner, Manuel; Keller, Katharina; et al. (Geburtshilfe und Frauenheilkunde, 2025)
This review summarizes the latest developments for the treatment of patients with early-stage breast cancer. Most of the clinically relevant changes were the result of using immune checkpoint inhibitors to treat patients with triple-negative breast cancer (TNBC) and CDK4/6 inhibitors to treat patients with hormone receptor-positive, HER2-negative (HRpos/HER2neg) tumors and a high risk of recurrence. Recent studies are presenting more and more data with long follow-up times and integrating translational analyses to evaluate new biomarkers such as circulating tumor DNA (ctDNA). This review article summarizes the latest developments published in recent months and puts the findings in context.
CRIS-Team Scopus Importer:2025-05-30
Keywords: biomarker; breast cancer; clinical studies; early breast cancer

Update Breast Cancer 2024 Part 3 – Patients with Advanced Stage Breast Cancer - Lüftner, Diana; Kolberg, Hans Christian; Hartkopf, Andreas D.; Fehm, Tanja N.; Welslau, Manfred; Müller, Volkmar; Schütz, Florian; Fasching, Peter; Jackisch, Christian; Marme, Frederik; Keller, Katharina; Hörner, Manuel; et al. (Geburtshilfe und Frauenheilkunde, 2025)
The use of CDK4/6 inhibitors, the new PI3K/AKT-kinase inhibitors, selective estrogen receptor-degraders (SERDs), antibody-drug conjugates, immune therapies and PARP inhibitors in recent years has resulted in a marked change in the therapy landscape for patients with advanced stage breast cancer. CDK4/6 inhibitors, trastuzumab deruxtecan, and sacituzumab govitecan have all been shown to provide significant overall survival benefits compared to conventional chemotherapy. Other substances are also showing promising results and hold out the hope that further analysis of the overall survival benefits will be available in the near future. The speed at which studies are now being carried out has markedly increased, and conferences and specialist journals are now constant sources of new information. This review summarizes the most recent publications and conference presentations on the treatment of patients with advanced stage breast cancer.
CRIS-Team Scopus Importer:2025-05-30
Keywords: advanced breast cancer; breast cancer; clinical studies; prognosis